Crossability between cultivated rice {Oryza sativa) and common wild rice (O. rufipogon) and characterization of F1 and F2 populations - Sunisa Niruntrayakul (2018)
Gene flow between cultivated and wild rice is considered to be the origin of weedy rice, a threat to rice production in Thailand since 2001. The present study determined the degree of cross compatibility between four cultivated rice (Oryza sativa) varieties, namely, two high yielding varieties, CNT1 and SPR1 and two pure lined traditional varieties, KDMLl05 and RD6, and two common wild rice biotypes (O. rufipogon) from Kanchanaburi (KC) and Nakorn Nayok (NY). The hybrid progeny in the F1 and F2 generations were characterized for selected traits. The cultivated and wild rice cross fertilized with different degrees of compatibility between different parents, with higher seed set in crosses involving the high yield varieties than with the traditional varieties. The F1 hybrids were mostly fertile, exhibiting wild traits of spikelet awning, seed shattering, and red pericarp with hybrid vigour in panicle size from crosses between cultivated and NY wild rice, followed by transgressive segregation in the same characteristics in the F2's. Genotypic effects of the cultivated and wild rice parents were shown in segregation of flowering time, culm length, and seed shattering of the F 2 plants. Segregation of seed shattering pattern in the F2 differed between the wild rice parents; offspring of NY shattered their seed completely, while some of those of KC did not all shatter their seed. Genotypic effects of the wild and cultivated rice parents, especially in those traits important to survival and dispersal, suggest a range of possible recombinations that may need to be considered in effective control of the weedy rice and for the conservation of wild rice in situ.